Parental Internalizing Psychopathology and PTSD in Offspring after the 2012 Earthquake in Italy - Barbara Forresi; Marcella Caputi; Simona Scaini; Ernesto Caffo; Gabriella Aggazzotti; Elena Righi (MDPI AG, 2021)
Post-traumatic stress disorder (PTSD) is common in youths after earthquakes, with parental psychopathology among the most significant predictors. This study investigated the contribution and the interactional effects of parental internalizing psychopathology, the severity of exposure to the earthquake, and past traumatic events to predict PTSD in offspring, also testing the reverse pattern. Two years after the 2012 earthquake in Italy, 843 children and adolescents (9-15 years) living in two differently affected areas were administered a questionnaire on traumatic exposure and the UCLA PTSD Reaction Index. Anxiety, depression, and somatization were assessed in 1162 parents through the SCL-90-R. General linear model showed that, for offspring in the high-impact area, predictors of PTSD were earthquake exposure, past trauma, and parental internalizing symptoms, taken individually. An interaction between earthquake exposure and parental depression or anxiety (not somatization) was also found. In the low-impact area, youth PTSD was only predicted by earthquake exposure. The reverse pattern was significant, with parental psychopathology explained by offspring PTSD. Overall, findings support the association between parental and offspring psychopathology after natural disasters, emphasizing the importance of environmental factors in this relationship. Although further research is needed, these results should be carefully considered when developing mental health interventions.